Analisis Pemeliharaan Spring Load Cell Pada Mesin Roto Packer Di PT. Semen Indonesia (Persero) Tbk - Yvonne Christy Julyandini; I Nyoman Lokajaya (Jurnal Kendali Teknik dan Sains, 2023)
PT. Semen Indonesia (Persero) Tbk is a company that produces cement and runs the production process 24 hours a day. The company uses Roto Packer in its packaging process. In carrying out machine maintenance efforts, the company has implemented a maintenance system, namely preventive maintenance. However, even though preventive maintenance has been carried out, the company still experiences downtime on the spring load cell components. Therefore, it is necessary to carry out an analysis in order to determine the time between breakdowns, breakdown times, and arrange optimal maintenance schedules for spring load cell components. This study uses the Reliability Centered Maintenance (RCM) method with the Kolmogorov-Smirnov test to develop preventive maintenance activities that have been scheduled by the company. The results obtained, for the spring load cell component, component replacement must be carried out every 4 days with a replacement time of 49 minutes and a reliability of 39.87%.